Meta-analysis of the effects of management factors on Miscanthus × giganteus growth and biomass production - Miguez, Fernando E. (2008)
Biomass crops in the U.S. have the potential to reduce the dependence on foreign energy supply, to lower net greenhouse emissions, and to diversify agroecosystems. Miscanthus × giganteus has been extensively researched in Europe but the response to key agronomic management factors has not been summarized. In this study we have collected most of the relevant and up to date European literature on the response of dry biomass production to planting density and nitrogen (N) fertilizer and we provide quantitative estimates of the effect of these practices. The data were analyzed through non-linear mixed models which take into account the hierarchical structure of the data due to variability among countries, locations and years. M. × giganteus responded to N fertilizer only after the third growing season and planting density only had a significant effect on the second growing season. The similarity among growth curves, when dry biomass production was analyzed as function of thermal time, shows the stability of the cropping system against other environmental factors.